Influence of deformations with higher multiplicities on the barrier height of nuclei - Denisov, V.Yu.; Margitych, T. O. (Reports of the National Academy of Sciences of Ukraine, 2015)
The interaction energy between two nuclei with regard for the linear terms associated with the quadrupole, octupole, and hexadecapole deformations of nuclei surfaces and with quadratic terms of the quadrupole deformation parameter is studied. The Coulomb and nuclear interaction energies, as well as the deformation energies of the surfaces of both nuclei, are considered at the evaluation of the interaction energy. It is shown that the barrier and the interaction energy of two nuclei depend on the deformations parameters. The minimal barrier heights of two nuclei and the values of deformations that correspond to them are evaluated. The difference between the barrier height of spherical nuclei and the lowest barrier height related to deformed nuclei, in view of the quadrupole, octupole, and hexadecapole deformations of nuclei surfaces, increases with the mass and the charge of interacting nuclei. The strongest impact on the barrier height is given by the quadrupole deformation, the octupole deformation slightly reduces the barrier, and the hexadecapole deformation weakly affects the value of minimal barrier height.